Miescher's cheilitis: Surgical management and long term outcome of an extremely severe case. (2017) - Innocenti, Alessandro; Innocenti, Marco; Taverna, Cecilia; Melita, Dario; Mori, Francesco; Ciancio, Francesco; De Giorgi, Vincenzo; Parronchi, Paola; Vultaggio, Alessandra; Matucci, Andrea
Abstract: Introduction: Miescher's cheilitis is clinically characterized by persistent swelling of the lip(s). Its pathogenesis is still unknown. Histopathologically is characterized by sub-epithelial edema, increased number of dilated lymphatic vessels and an inflammatory infiltrate and/or non-caseating/non- necrotic granulomas. Even if the disorder must be controlled by medical therapy, surgery may be required to treat most severe cases. Presentation of the case: We report a 30-year-old man who presented a persistent swelling of both lips since 8 years, previously treated with intralesional steroid and immunosuppressive therapy. Clinical examination did not show facial nerve palsy or other associated conditions. On the base of clinical and histopathological findings, a diagnosis of Miescher's syndrome was made. Patient underwent Conway's reduction cheilopasty repaired with local flaps. At one-year follow-up, the patient does not show local recurrence of the deformity; both oral continence and lip sensation are preserved. Discussion: Because of its extreme rarity and unknown etiopathogenesis, Miescher's cheilitis receives poor attention and may often remain misdiagnosed. Several medical therapies are proposed, in particular steroids and immunosuppression. Even if medical therapy remains the main treatment, surgery may be required. Conclusion: Satisfactory results have been obtained combining medical therapy and surgical approach.